2020
DOI: 10.1038/s41598-020-58688-y
|View full text |Cite
|
Sign up to set email alerts
|

A 4-gene signature from histologically normal surgical margins predicts local recurrence in patients with oral carcinoma: clinical validation

Abstract: Prognostic biomarkers for recurrence of Oral Squamous Cell Carcinoma (OSCC) are urgently needed. We aimed to independently validate a 4-gene expression signature (MMP1, COL4A1, P4HA2, THBS2) predictive of OSCC recurrence risk. Gene expression was measured using Nanostring nCounter ® in 245 histologically normal surgical resection margins from 62 patients. Association between risk scores for individual patients and recurrence was assessed by Kaplan-Meier analysis. Signature performance was quantified by concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Nanostring has been shown to have high sensitivity and specificity and assay reproducibility, which are critical features of clinical utility [40]. More recently, this technology was used to develop a molecular assay that determines the risk of recurrence in oral cancer [41] and triple-negative breast cancer patients [42]. Our results, along with others, suggest that the Nanostring assay is useful for molecular testing development across multiple tumor types, including early detection of lung cancer.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Nanostring has been shown to have high sensitivity and specificity and assay reproducibility, which are critical features of clinical utility [40]. More recently, this technology was used to develop a molecular assay that determines the risk of recurrence in oral cancer [41] and triple-negative breast cancer patients [42]. Our results, along with others, suggest that the Nanostring assay is useful for molecular testing development across multiple tumor types, including early detection of lung cancer.…”
Section: Discussionmentioning
confidence: 54%
“…The Nanostring nCounter ® assay used 200 ng of RNA from each sample. This assay was performed at the Princess Margaret Genomics Centre ( ), according to the manufacturer’s protocol, and as described in previous studies [ 41 ]. The nSolver™ Analysis Software ( ) was used for global normalization of miRNA expression data against positive and negative controls, exogenous and stable endogenous controls, and to calculate fold change (FC) and associated p -values for deregulated miRNAs in patient plasma compared to reference, healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…The roles played by LBH in OSCC pathogenesis remain hitherto obscure. MMP1 and BMP2 are known to modulate cell activity and the tumor microenvironment, as well as being factors associated with OSCC relapse [5,46,47]. This study identifies the up-regulation of MIR31HG in cytobrushed OPMD samples.…”
Section: Introductionmentioning
confidence: 83%
“…This study has identified a MIR31HG induced differential gene expression profile that is independent of miR-31. MMP1 and BMP2, which are prognostic factors of HN-SCC [5,46,47], and are up-regulated by MIR31HG at the transcription level. During the senescence induced by oncogenic stimulation, cytosolic MIR31HG would seem to increase IL1A protein levels, which then transactivates a panel of secretory molecules such as MMP1 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite instability Surgical margins 61 mRNA Nanostring/4-gene signature Surgical margins 64 Methylated DNA Quantitative methylation-specific PCR Surgical margins 65 DNA NGS: missense mutations TP53 (EA score), intratumoral heterogeneity (MATH)…”
Section: Dnamentioning
confidence: 99%